Prescribing pattern of anti-hypertensive drugs: A prospective study - Nisha Rani S S; Nelta S Tharakan; Gomathi Swaminathan; Sattanathan .K; Shanmuga Sunadaram .R; Sambathkumar .R (International Journal of Pharmacy and Analytical Research, 2015)
The sources of drug utilization data vary from country to country depending on the level of sophistication of record keeping, data collection, analysis and reporting and the operational considerations of the health care system. So in most part of our country the prescribing pattern of antihypertensive drugs by different physicians is not in compliance with that of the standard guidelines. The purpose of this study was to evaluate the prescribing pattern of antihypertensive drugs and to determine the type of drugs commonly prescribed i.e. either monotherapy or combination drugs. This observational prospective study was conducted in erode for a time period of 4 months. The maximum percentage of male and females with hypertension was found at the age group of 50-60 years. As monotherapy ACE-inhibitors (34%) were the most commonly prescribed antihypertensive followed by calcium channel blockers (18%) and beta blocker (12%). Among combination therapy often 2 drug combinations were prescribed, the most common combination was ACE-inh + CCB (8%), followed by beta-blocker + CCB (6%). Hence we concluded that underutilization of diuretics and inadequate oral instructions by clinical pharmacist are found to be the limitations of the present prescribing pattern and hence, an intervention study is needed to improve the current prescribing practice in clinical use of hypertension management.